KNOWLEDGE ECONOMY AND THE TRANSFORMATION OF EDUCATIONAL SYSTEMS: STRATEGIES FOR BUILDING HUMAN CAPITAL IN THE DIGITAL AGE-A FIELD STUDY AT THE COLLEGE OF ADMINISTRATION AND ECONOMIC - Naeem Hameed Mahoud (Scholar Express Journals, 2025)
This study aims to explore the relationship between the knowledge economy and the transformation of educational systems by analyzing strategies for building human capital within the university environment. This inquiry is conducted in the context of the rapid digital transformations characterizing the modern era. The College of Administration and Economics at the University of Thi-Qar was selected as the field of study due to its role as an educational setting striving to integrate into the digital education system and to harness digital tools in developing human competencies
Keywords: Knowledge Economy; Educational Systems; Human Capital